One night expectations - LaQuette (LaQuette. Devereaux Inc., 2022)
When her grandfather meddles in the billion-dollar development deal she's closing for the family company, Amara Devereaux-Rodriguez feels betrayed...and rebellious. A chance encounter with Lennox Carlisle is just the kind of trouble she's looking for. But their night together soon becomes a threat to Amara's aspirations because the mayoral contender has the power to quash the Devereaux deal. And now Amara's pregnant with his child. Can she quench the fire for Lennox that could send their lifelong ambitions up in flames?